Addressing Maladaptive Coping Strategies of Local Communities to Chang es in Ecosystem Service Provisions Using the DPSIR Framework - Ehara, Makoto; Hyakumura, Kimihiko; Sato, Ren'ya; Kurosawa, Kiyoshi; Araya, Kunio; Sokh, Heng; Kohsaka, Ryo (Ecological Economics, 2018)
The Driver-Pressure-State-Impact-Response (DPSIR) framework has been a pplied to various environmental problems at multiple spatial and tempo ral scales and attempts have been made to conceptually improve the fra mework to encompass various stakeholder perspectives. However, recent literature experiences in the field have challenged the inclusive char acter of the framework applications. In particular, the framework's in ability to incorporate the aggregated informal responses of people aff ected by changes in ecosystem service provisions has not been fully ad dressed. This limits the framework's validity in categorizing and diss eminating information for addressing particular environmental challeng es. Herein, we address this problem by analyzing a case study of defor estation and its impact on non-timber forest product collections by ru ral residents in Cambodia. We incorporate the concept of maladaptive c oping strategies into the DPSIR framework and then further elaborate N ess et al.'s (2010) approach of merging the DPSIR framework with Häger strand's (2001) system of nested spatial domains. This conceptualizes the incorporation of the aggregated informal responses into the system , as exemplified in the case study.
Keywords: DPSIR framework; Ecosystem services; Maladaptive coping strategy; Nested spatial domains